Biocompatibility and cellular compatibility of decellularized tracheal matrix derived from rabbits. Issue 9 (September 2019) - Zhang, Fangbiao; Wang, Zhihao; Zheng, Chunhui; Zhao, Chun; Shi, Hongcan; Pan, Shu; Zhang, Weidong
Objective: To study the different concentrations of Triton X-100 and nuclease needed to remove cells from the tracheal matrix of rabbits and analyse their biocompatibility and cellular compatibility. Methods: Fifty tracheas were harvested from donor New Zealand rabbits. Thirty tracheas were randomly divided into five groups (n = 6 each). The tracheas in group A were untreated and served as a control group, and those in groups B, C, D and E were treated with different concentrations of Triton X-100 (1%, 2%, 3% and 4%), respectively. The tracheas of the five groups were assessed by histological observation, scanning electron microscopy and mechanical evaluation. The remaining 20 donor tracheas, which were divided into a control group and an optimally decellularized group, were used for xenogeneic transplantation and cell seeding. Results: Many epithelial cells and cartilage cells were observed in the tracheas of group A. There were fewer cartilage cells in the tracheas of groups C, D and E than in the tracheas of groups A and B under histological observation. In scanning electron microscopy, there were many ciliated epithelial cells in the tracheas of group A; in groups B and C, the ciliated epithelial cells disappeared, but the basement membrane was intact. The basement membranes were broken in the tracheas of groups D and E. Implanted decellularized tracheas showed good biocompatibility. Bone marrow mesenchymal stem cells grown in the decellularized tracheal matrix grew well. Conclusion: Decellularized tracheal matrix obtained from rabbits by 2% Triton X-100 may be suitable for the construction of tissue-engineered trachea because of its favourable morphological and biomechanical properties as well as its biocompatibility and cellular compatibly.